Identities, Society And Power - Gulalp, Haldun (ISTANBUL UNIV, 2009)
Offering a sociological approach to the formation of identities, this paper examines current debates in Turkey and argues that the modernist opponents of identity politics, such as proponents of nationalism and the class perspective, are themselves implicated in the politics of identity.
Keywords: Identity Politics; Nationalism; Postmodernity; Democracy; Government & Law